Варвары Крыма: [фантастичкский роман] / А. Левицкий, А. Бобл - Левицкий Андрей (Технотьма, 2010)
Экземпляры: абонемент (20140926) / Инвентарный номер: 40423 / Цена: 175.00 / Авт.знак: Л 37 / ГРНТИ: 17 / ББК: 84(2Рос-Рус)6 -44